DESIGN AND ESTABLISHMENT AND TECHNICAL DOCUMENTATION FOR THE CONSTRUCTION AND REPAIR OF PIPELINES AND ITS INSPECTION - Martyniuk, R. Т. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
All works on construction and repair of pipelines, as well as any industrial object are constructed according to the projects developed by the state design organizations. The design is guided by: industry instructions on the procedure for development, approval and approval of design and estimate documentation for the construction of enterprises, buildings and structures and instructions for design and construction; normative documents on norms of technological design, building norms and rules, catalogs of construction works; standards for building materials and parts; estimated standards for determining the estimated cost of construction and information on new technological and ancillary equipment.